The Relationship Between Climate and Dengue Hemorrhagic Fever Incidence Rate in Malang Regency In 2022-2024 - Pramono, Aticobhita C; suprijandani, Suprijandani; marlik, Marlik; Hermiyanti, Pratiwi (UI Scholars Hub, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that poses a public health problem in tropical regions and is influenced by climatic factors such as temperature, rainfall, humidity, and wind speed. In 2023, Malang Regency recorded 1,018 cases with an incidence rate (IR) of 38.2 per 100,000 population. This study aims to analyze the relationship between climatic factors and the DF IR for the 2022–2024 period using an ecological design and Spearman’s correlation analysis. Climate data were obtained from the BMKG, while DF data were obtained from the Health Office. The results showed that only air temperature was significantly associated (p = 0.032), while rainfall, humidity, and wind speed showed no significant association (p > 0.05). Temperature can serve as an early warning indicator. High temperatures should be prioritized as the optimal time for implementing control activities, such as community education and intensive Mosquito Larval Control (PSN). Keywords: Dengue Hemorrhagic Fever, Climate, Incidence Rate